Detrital stoichiometry as a critical nexus for the effects of streamwater nutrients on leaf litter breakdown rates. Issue 8 (1st August 2015) - Manning, David W. P.; Rosemond, Amy D.; Kominoski, John S.; Gulis, Vladislav; Benstead, Jonathan P.; Maerz, John C.
Abstract : Nitrogen (N) and phosphorus (P) concentrations are elevated in many freshwater systems, stimulating breakdown rates of terrestrially derived plant litter; however, the relative importance of N and P in driving litter breakdown via microbial and detritivore processing are not fully understood. Here, we determined breakdown rates of two litter species, Acer rubrum (maple) and Rhododendron maximum (rhododendron), before (PRE) and during two years (YR1, YR2) of experimental N and P additions to five streams, and quantified the relative importance of hypothesized factors contributing to breakdown. Treatment streams received a gradient of P additions (low to high soluble reactive phosphorus [SRP]; ~10–85 μg/L) crossed with a gradient of N additions (high to low dissolved inorganic nitrogen [DIN]; ~472–96 μg/L) to achieve target molar N:P ratios ranging from 128 to 2. Litter breakdown rates increased above pre‐treatment levels by an average of 1.1–2.2× for maple, and 2.7–4.9× for rhododendron in YR1 and YR2. We used path analysis to compare fungal biomass, shredder biomass, litter stoichiometry (nutrient content as C:N or C:P), discharge, and streamwater temperature as predictors of breakdown rates and compared models containing streamwater N, P or N + P and litter C:N or C:P using model selection criteria. Litter breakdown rates were predicted equally with either streamwater N or P ( R 2 = 0.57). In models with N or P, fungal biomass, litter stoichiometry, discharge, and shredder biomass predicted breakdown rates; litter stoichiometry and fungal biomass were most important for model fit. However, N and P effects may have occurred via subtly different pathways. Litter N content increased with fungal biomass (N‐driven effects) and litter P content increased with streamwater P availability (P‐driven effects), presumably via P storage in fungal biomass. In either case, the effects of N and P through these pathways were associated with higher shredder biomass and breakdown rates. Our results suggest that N and P stimulate litter breakdown rates via mechanisms in which litter stoichiometry is an important nexus for associated microbial and detritivore effects.